Implementasi Program Pekarangan Pangan Lestari (P2L) di Kecamatan Curug Kota Serang Provinsi Banten - ifda roflianti; Amirudin, Suwaib; Rizkiyani, Tiwi (LPPM STIA Banten, 2025)
Curug Sub-district of Serang City is the sub-district in Serang City that is most vulnerable to food insecurity, therefore through the P2L program the community is empowered to realize food security. The research method used in this research is a qualitative method with a descriptive approach. Data collection techniques used interviews, observation, and documentation studies. Analyzed with data analysis techniques through data collection, data reduction, data presentation, and conclusion drawing. Data validity testing is done through triangulation, membercheck, and ethical consideration. The focus of this research is on the Implementation of the Sustainable Food Yard Program (P2L) in Curug District, Serang City, Banten Province. The results showed that the implementation of the Sustainable Food Yard (P2L) program in Curug District is still not running optimally. This is because there are still some shortcomings and obstacles that occur such as the lack of program assistants, the cessation of planting activities in some KWT, the decline in member activeness, the availability of minimal facilities and infrastructure, poor land loan agreements, inadequate cash availability. Therefore, the Sustainable Food Yard program in Curug District, Serang City requires improvement and this is done by collaborating between various parties, both DKP3, extension workers at BPP, and KWT as program beneficiaries, so that the implementation of KWT can run well.